PENGARUH MODEL PEMBELAJARAN SAVI BERBANTUAN MEDIA LINGKUNGAN TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR IPA PADA SISWA KELAS V SEKOLAH DASAR GUGUS I MASBAGIK SELATAN LOMBOK TIMUR - Made Ayu Pransisca; Munawir Gazali (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This study was aimed at finding out the effect of problem learning SAVI model of media assist environment to scientific attitudes and learning outcomes of science the fifth grade students of elementary school cluster 1 south Masbagik. This study used a quasi-experiment design with Single Factor Independent Groups Design. The population consisted of 201 students. The sample was 65 students determined by random sampling technique. The data on the students scientific attitude were collected with an questionnaire. The data on the students’ science learning outcomes were collected with a test. The data were analyzed using MANOVA aided with SPSS 16.00 for windows. The results showed that, First, the students’ scientific attitude of those who joined the problem Savi learning model of media assist environment was significantly better than that of those who joined conventional teaching model (F=15.847; p < 0.05); secondly, the students’ science learning outcomes of those who joined problem Savi learning model of media assist environment was significantly better than those who joined conventional teaching model (F=39.123; p < 0.05) and thirdly, simultaneously, scientific attitude and science learning outcomes of the students who joined problem Savi learning model of media assist environment was significantly better than that of those who joined conventional teaching model (F= 31.207; p < 0.05).